2014
DOI: 10.1016/j.jnnfm.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Yield stress fluids method to determine the pore size distribution of a porous medium

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. b s t r a c tIn this paper a new method is presented in order to determine the pore size distribution in a porous medium. This original technique uses the rheological properties of some non-Newtonian yield stress fluids flowing through the porous sample. This technique is based on the capillary bundle model (like the other classical methods) which, despite its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…One of these is the experimental work of Chase and Dachavijit (2005), which uses a packed column containing spherical glass beads, where it is found that a scaled Buckingham-Reiner equation may be used to model at least this type of particulate porous medium. A second is the analysis of Oukhlev et al (2014) which shows how a Bingham fluid may be used to determine the pore size distribution within a medium. Their method was tested successfully on a medium consisting of pores which satisfy a Gaussian distribution.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is the experimental work of Chase and Dachavijit (2005), which uses a packed column containing spherical glass beads, where it is found that a scaled Buckingham-Reiner equation may be used to model at least this type of particulate porous medium. A second is the analysis of Oukhlev et al (2014) which shows how a Bingham fluid may be used to determine the pore size distribution within a medium. Their method was tested successfully on a medium consisting of pores which satisfy a Gaussian distribution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that one can therefore obtain a representative pore radius distribution of a given porous medium from experimental data relating flow rate to pressure gradient Q(∇ P) (Ambari et al 1990). The experimental feasibility of this method (called yield stress method or YSM) was investigated by several authors using various YSF and porous media (Malvault 2013;Rodriguez de Castro et al 2014;Oukhlef et al 2014;Rodriguez de Castro et al 2016). Moreover, the bundle of capillaries model is often used to exploit data coming from capillary pressure measurements using mercury injection experiments.…”
Section: Introductionmentioning
confidence: 99%
“…To study the nature of the airproofing pressure and pneumatically convert it to the effective stress in the mechanism, it should be considered from the surface tension of the water in the porous medium [15]. A capillary bundle model is very commonly used to study the movement of water in the porous medium [16,17]. Pore connectivity in the media is observed as a capillary in the model [18].…”
Section: Physical Meaning Of the Airproofing Pressure Of The Filtermentioning
confidence: 99%